2010
DOI: 10.1155/2010/173274
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polyphenols, -Carotene, and Lycopene in the Antioxidative Action of the Extracts of Dried, Edible Mushrooms

Abstract: One of the nutritional benefits of mushrooms is the presence of bioactive secondary metabolites which have been reported to exert various beneficial effects in vivo. Therefore, we selected thirteen frequently consumed species of Polish mushrooms and determined the concentration of polyphenols, flavonoids, β-carotene, and lycopene in aqueous and methanolic extracts of dried fruiting bodies as well as their reducing power and ability to scavenge ABTS cation radical. We found that the concentration of antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
4
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 53 publications
5
36
4
4
Order By: Relevance
“…Findings of carotenoid content in the Ganoderma species in good amount made them important at par with fruits and vegetables (Mangels et al 1993). A higher amount of Beta carotene and lycopene was exhibited in these species and corroborated with the reports of Robaszkiewicz et al (2010), Pal et al (2010) and Celik et al (2014). Ascorbic acid is considered to exert a protective role against many oxidative stress related ailments such as cardiovascular, cancer, neurodegenerative problems and cataract (Halliwell 1996).…”
Section: Resultssupporting
confidence: 80%
“…Findings of carotenoid content in the Ganoderma species in good amount made them important at par with fruits and vegetables (Mangels et al 1993). A higher amount of Beta carotene and lycopene was exhibited in these species and corroborated with the reports of Robaszkiewicz et al (2010), Pal et al (2010) and Celik et al (2014). Ascorbic acid is considered to exert a protective role against many oxidative stress related ailments such as cardiovascular, cancer, neurodegenerative problems and cataract (Halliwell 1996).…”
Section: Resultssupporting
confidence: 80%
“…Previous study by Stahl et al (1998) showed that lycopene was three times more efficient than β-carotene in preventing lipid peroxidation in multi lamellar liposomes. Besides, in previous study by Robaszkiewicz et al (2010) it was established that the content of lycopene was far lower than the concentration of β-carotene in the mushrooms where 0.0265 mg 100 g and ∼24.31 mg 100 g -1 in tomato. In the present study, phenol was the major antioxidant component followed by β-carotene, lycopene and flavonoids (Table 1).…”
Section: Lycopene and β-Carotene Content (Carotenoids)mentioning
confidence: 94%
“…The total phenolic contents of M. conica Pers. were higher than those of Pleurotus ostreatus (1.44 mg GAE/g DW), Cantharellus cibarius (0.77 mg GAE/g DW) [30], Agaricus arvensis (2.83 mg GAE/g DW) and Saarcodon imbricatum (3.76 mg GAE/g DW) [31], but lower than the ethanol extracts of Portabella (10.65 mg GAE/g DW) and Crimini (9.89 mg GAE/g DW) [32]. Note: A-C, different uppercase letters indicate significant differences of free phenolics in the same column (p<0.05); a-c, different lowercase letters indicate significant differences of bound phenolics in the same column (p<0.05).…”
Section: Total Phenolic Content In Morchella Conica Persmentioning
confidence: 62%
“…Subsequently, medium containing different concentrations of free polyphenol extract (25, 50, 75, 100, 125, 150, 175, 200, 225, 250 μg/mL) and bound polyphenol extract (10,20,30,40, 50, 60, 70, 80, 90, 100 μg/mL) was added (100 μL/well), followed by incubation at 37°C for another 24 h. The medium was then removed, and the plate was washed with PBS (100 μL/well). Thereafter, 50 μL/well of methylene blue solution (prepared with 0.6% methylene blue, 0.67% glutaraldehyde, and 98% HBSS) was added for staining.…”
Section: Cytotoxicitymentioning
confidence: 99%